Organic value chain study: Opportunities, constraints and strategies for promotion of organic horticulture in Kerala - V, Abhilash; Kashyap, Poonam; Ravisankar, N; Panwar, A S; Prusty, A K; Shamim, M (Indian Horticulture, 2022)
Organic agriculture is one of the production system which is supportive to the environment. The scope and potential of organic agriculture especially of fruits and vegetable farming is continuously increasing in today's scenario. Organic agriculture in India is in a growth stage with abundant opportunities and risks. Advancements in agriculture related technologies and management are crucial for accelerated and sustainable development of Indian organic agriculture sector. Integrated Organic Farming System (IOFS) models promises to meet 70-80% of organic inputs within farms and should be given impetus for promotion. According to All India Network Programme on Organic Farming (AI-NPOF), organic production is more of a description of the agricultural methods used on a farm, rather than food which combines tradition, innovation and science. Initiatives to introduce cold chain, food parks and other modern marketing strategies, and integrating value chain in fruits and vegetables have come as a fresh boost to Indian agriculture and increased the pace of transformation of the sector into a commercial and market driven enterprise. The analysis of the behaviour and perception of organic farmers, value addition centres and consumers in Palakkad, Kerala reveals that organic fruits and vegetables have huge potential inside and outside Kerala. So the value addition centres need to grow up accordingly to the new age requirement which can benefit both organic farmers as well as consumers.